Cell Reprogramming, IPS Limitations, and Overcoming Strategies in Dental Bioengineering - Gaskon Ibarretxe; Antonia Alvarez; Maria-Luz Cañavate; Enrique Hilario; Maitane Aurrekoetxea; Fernando Unda (Stem Cells International)
The procurement of induced pluripotent stem cells, or IPS cells, from adult differentiated animal cells has the potential to revolutionize future medicine, where reprogrammed IPS cells may be used to repair disease-affected tissues on demand. The potential of IPS cell technology is tremendous, but it will be essential to improve the methodologies for IPS cell generation and to precisely evaluate each clone and subclone of IPS cells for their safety and efficacy. Additionally, the current state of knowledge on IPS cells advises that research on their regenerative properties is carried out in appropriate tissue and organ systems that permit a safe assessment of the long-term behavior of these reprogrammed cells. In the present paper, we discuss the mechanisms of cell reprogramming, current technical limitations of IPS cells for their use in human tissue engineering, and possibilities to overcome them in the particular case of dental regeneration.